AgIn5S8/ZnS Quantum Dots for Luminescent Down-Shifting and Anti-Reflective Layer in Enhancing Photovoltaic Performance - Kong, Mengqin; Osvet, Andres; Barabash, Anastasia; Zhang, Kaicheng; Hu, Huiying; Elia, Jack; Erban, Christof; Yokosawa, Tadahiro; Spiecker, Erdmann; Batentschuk, Miroslaw; Brabec, Christoph (ACS Applied Materials and Interfaces, 2023)

Automated Synthesis of 1-Tetradecylphosphonic Acid-Capped FAPbBr3 Nanocrystals for Light Conversion in Display Applications - Hu, Huiying; Shi, Hongyang; Zhang, Jiyun; Hauch, Jens; Osvet, Andres; Brabec, Christoph (ACS Applied Nano Materials, 2024)
Perovskite nanocrystals (NCs) have garnered increasing attention as light-emitting materials owing to their high photoluminescence quantum yields (PLQY) and narrow full width at half-maximum (fwhm). However, the poor stability hinders their practical application in displays. In this work, we investigate the photostability of FAPbBr3 NCs with the modification of 1-tetradecylphosphonic acid (TDPA). Employing a high-throughput approach, the optimized FAPbBr3/TDPA NCs reached a sufficiently high PLQY of 76% with a narrow band emission of 20 nm, as opposed to 45% PLQY for FAPbBr3/oleic acid NCs. Due to the strong passivation of TDPA on the perovskite surface, NC-filled polymeric binder layers exhibit excellent photostability under environmental conditions. The optimal samples maintained 95% of the initial PL intensity after continuous intense irradiation.
CRIS-Team Scopus Importer:2024-04-26
Keywords: ligand; light conversion; perovskite nanocrystal; PLQY; stability

Direct Observation of Stable Negative Capacitance in SrTiO3@BaTiO3 Heterostructure - Wang, Zhongyang; Li, Hongyu; Hu, Huiying; Fan, Yuqi; Fan, Runhua; Li, Baowen; Zhang, Jiaoxia; Liu, Hu; Fan, Jincheng; Hou, Hua; Dang, Feng; Kou, Zongkui; et al. (Advanced Electronic Materials, 2019)
Negative capacitance in ferroelectrics has seem remarkable progress in recent years. However, direct measurement of negative capacitance has so far been a challenge due to its instable characteristic in the electrostatic field. An ingenious method to design stable negative capacitance by dielectric resonance under high-frequency alternating electric fields is demonstrated. The well-pronounced dielectric resonance and electrical property in BaTiO3/SrTiO3 (BT/ST) bulk ceramics consisted of epitaxial core-shell particles are studied. As the negative capacitance can be considered as an inductive behavior, the dielectric resonance of permittivity induced by a LC resonance can be occurred. The dielectric resonance can be described by the Lorentz model and explained by Fano-like resonance of TO2 phonon in BT. In addition, lowest resonant frequency is observed at effective Curie temperature. Benefiting from negative capacitance in the BT/ST ceramics, both high permittivity and negative permittivity are accompanied with low losses around the resonant frequency, which is useful for developing capacitors and metamaterials. Significantly, this work will provide an initiative avenue to obtain explicit negative capacitance of ferroelectrics in the frequency spectrum.
CRIS-Team WoS Importer:2019-12-27

Engineering Stable Perovskite Quantum Dot Films for High Color Purity Display Applications - Hu, Huiying; Levchuk, Ievgen; Kalkowski, Felix; Elia, Jack; Osvet, Andres; Brabec, Christoph (ACS Energy Letters, 2023)
Lead halide perovskite nanocrystals (NCs) are the most promising candidates for displays satisfying the Rec. 2020 UHDTV color standard. However, moisture sensitivity currently limits light-emitting applications requiring color stability and purity. In this study, we propose a large-area FAPbBr3-based quantum dot brightness enhancing film (QDEF) strategy developed in our group five years ago. The combination of a polymeric binder tailored to the ligands optimized perovskite NCs for light conversion and demonstrates QDEF applications with 91% coverage of Rec. 2020 standard in tablet displays, using polyhedral oligomeric silsesquioxane-capped FAPbBr3 as the green emitter and K2SiF6: Mn4+ (KSF) as a red emitter. Remarkably, our films operating in displays showed 4 year stability without lead leakage. Even without barrier protection, the unpackaged QDEF maintained 55% of its initial performance. This highlights the importance of a dual stabilization strategy for extending operational and shelf lifetimes of advanced functional perovskite composites.<br

Enhanced Photostability of Lead Halide Perovskite Nanocrystals with Mn3+ Incorporation - Hu, Huiying; Fehn, Dominik; Barr, Maissa; Harreiß, Christina; Zhao, Yicheng; Meyer, Karsten; Osvet, Andres; Brabec, Christoph (ACS Applied Materials and Interfaces, 2024)
Recently, lead halide perovskite nanocrystals (NCs) have shown great potential and have been widely studied in lighting and optoelectronic fields. However, the long-term stability of perovskite NCs under irradiation is an important challenge for their application in practice. Mn2+ dopants are mostly proposed as substitutes for the Pb site in perovskite NCs synthesized through the hot-injection method, with the aim of improving both photo- and thermal stability. In this work, we employed a facile ligand-assisted reprecipitate strategy to introduce Mn ions into perovskite lattice, and the results showed that Mn3+ instead of Mn2+, even with a very low level of incorporation of 0.18 mol % as interstitial dopant, can enhance the photostability of perovskite binder film under the ambient conditions without emission change, and the photoluminescent efficiency can retain 70% and be stable under intensive irradiation for 12 h. Besides, Mn3+ incorporation could prolong the photoluminescent decay time by passivating trap defects and modifying the distortion of the lattice, which underscores the significant potential for application as light emitters.
CRIS-Team Scopus Importer:2024-05-17
Keywords: interstitial doping; passivation; perovskite nanocrystal; photoluminescence; photostability

Modified Synthesis of Cs4PbBr6 for Enhanced Purity and Quantum Yield and for Exploring Its Potential as a High Stokes Shift Material for Down-Conversion in Solar Cells - Darwish, Elshaimaa; Elia, Jack; Barabash, Anastasia; Hu, Huiying; Batentschuk, Miroslaw; Osvet, Andres (Advanced Engineering Materials, 2024)
Energy demands have kept increasing in recent years due to expanding human activity. Silicon solar cells offer an attractive renewable energy source while their external quantum efficiency (EQE) can still be enhanced; one way of doing this is by applying a photon energy downshifting layer. Herein, Cs4PbBr6 is applied as a downshifting layer; the Cs4PbBr6 is synthesized in the form of colloidal nanoparticles, and several modifications are introduced to the synthesis process, resulting in the enhancement of the photoluminescence quantum yield, improving the particle size distribution and reducing the CsBr impurities which appear as a side product during the synthesis of Cs4PbBr6. The application of the produced modified particles in the form of thin films on the top of Si solar cells shows an enhancement of the (EQE) of the solar cells when compared to the unmodified particles.
CRIS-Team Scopus Importer:2024-06-07
Keywords: 0D Cesium lead halide; down conversion; enhancing quantum yield; perovskite nanoparticles; silicon solar cells

Strain-activated light-induced halide segregation in mixed-halide perovskite solids - Zhao, Yicheng; Miao, Peng; Elia, Jack; Hu, Huiying; Wang, Xiaoxia; Heumüller, Thomas; Hou, Yi; Matt, Gebhard; Osvet, Andres; Chen, Yu-Ting; Tarragó, Mariona; de Ligny, Dominique; et al. (Nature Communications, 2020)
Light-induced halide segregation limits the bandgap tunability of mixed-halide perovskites for tandem photovoltaics. Here we report that light-induced halide segregation is strain-activated in MAPb(I1−xBrx)3 with Br concentration below approximately 50%, while it is intrinsic for Br concentration over approximately 50%. Free-standing single crystals of CH3NH3Pb(I0.65Br0.35)3 (35%Br) do not show halide segregation until uniaxial pressure is applied. Besides, 35%Br single crystals grown on lattice-mismatched substrates (e.g. single-crystal CaF2) show inhomogeneous segregation due to heterogenous strain distribution. Through scanning probe microscopy, the above findings are successfully translated to polycrystalline thin films. For 35%Br thin films, halide segregation selectively occurs at grain boundaries due to localized strain at the boundaries; yet for 65%Br films, halide segregation occurs in the whole layer. We close by demonstrating that only the strain-activated halide segregation (35%Br/45%Br thin films) could be suppressed if the strain is properly released via additives (e.g. KI) or ideal substrates (e.g. SiO2).<br